FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN INFORMASI AKUNTANSI DI UKM WIG KABUPATEN PURBALINGGA - Aditya Rahmawan; Eliada Herwiyanti; Siti Maghfiroh (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This study aimed to examine the factors that influence the use of accounting information in SMEs. The object of research is Wig UKM in Purbalingga Regency. From this research, it can be seen how education, business scale, business age, and accounting knowledge of the use of UKM Wig accounting information in Purbalingga. The number of respondents involved in this study was 82 people. Sampling using a purposive sampling method. Based on the results of research and data analysis using SPSS it was found that: (1) educational background did not have a significant negative effect on the use of accounting information, (2) the business scale had no significant positive effect on the use of accounting information, (3) the age of the business had no significant negative effect on the use of accounting information, and (4) accounting knowledge has a significant positive effect on the use of accounting information.